The RNA‐binding protein SORBS2 suppresses hepatocellular carcinoma tumourigenesis and metastasis by stabilizing RORA mRNA. (25th September 2019) - Han, Lili; Huang, Chen; Zhang, Shuqun
Abstract: Background: Numerous studies have revealed that dysregulation of RNA‐binding protein (RBP) expression is causally linked with human cancer tumourigenesis. However, the detailed biological effect and underlying mechanisms of most RBPs remain unclear. Methods: Expression of sorbin and SH3 domain‐containing 2 (SORBS2) in hepatocellular carcinoma (HCC) was detected by qRT‐PCR, immunohistochemistry assay and Western blot assay. Proliferation, migration, invasion and cell cycle progression of HCC cells were measured by 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, colony‐forming assay, Transwell assay and flow cytometry assay respectively. A xenograft model and metastatic model were established to evaluate the proliferation and metastasis of HCC cells in vivo. Western blot assays were performed to assess the expression of epithelial‐mesenchymal transition markers. Luciferase reporter assay, RNA immunoprecipitation and pull‐down assay elucidated the effect of SORBS2 on one of its downstream genes. Results: The expression of SORBS2 was significantly decreased in HCC and was associated with metastasis, advanced TNM clinical stage and poor clinical outcome of HCC patients. Furthermore, our results suggested that SORBS2 inhibited HCC cell proliferation, invasion, migration and EMT both in vivo and in vitro. Mechanistically, we revealed that retinoic acid receptor‐related orphan receptor (RORA) was a major target of SORBS2 and was critical to sustaining the antitumour effect of SORBS2 on HCC cells. SORBS2 reduced RORA mRNA degradation by directly binding to the 3′UTR of RORA mRNA. Conclusions: In this study, we found for the first time that SORBS2 contributed to the suppression of HCC tumourigenesis and metastasis via post‐transcriptional regulation of RORA expression as an RBP.